KEDUDUKAN HARTA BERSAMA DALAM PERKAWINAN MENURUT FIQIH DAN HUKUM POSITIF INDONESIA SERTA PRAKTEK PUTUSAN PENGADILAN AGAMA - Arifah S. Maspeke; Akhmad Khisni (Jurnal Hukum Khaira Ummah, 2017)
Property in marriage is one important factor, because it can be said as a mover of a married life. The property consists of inherited property, acquisition and joint property.In the fiqih is not known the term joint treasure, but the study of Indonesian scholars on joint property has given birth to the opinion that the joint property can be analogous to shirkah. The provisions on joint property in Indonesian positive law are regulated in Law Number 1 Year 1974 concerning Marriage and Compilation of Islamic Law. In Articles 96 and 97 of KHI, joint property is divided by two, each husband shall receive half of the common property as long as it is not specified otherwise in the marriage agreement. The Decision of the Religious Courts does not always adhere to the provisions of Article 97 of the Compilation of Islamic Law, but it can be casuistically different based on the principle of justice and usefulness.Keywords: Marriage, Joint Property, Religious Court Judgment